Artificial Intelligence in Colonoscopic Polyp Detection and Characterization: Merging Computer Technology and Endoscopic Skill for Better Patient Care - Uday C. Ghoshal; Saikat Chakrabarti; Mahesh K. Goenka (Journal of Digestive Endoscopy, 2023)
Artificial intelligence (AI) is a computer technology for mathematical modeling that uses nonlinear statistical analysis. While multilayer perceptron network is used for prediction of clinical outcome, convolutional neural network is used for detection of lesion in an image and its classification. In this issue of the journal, an article reviewed the impact of AI in colorectal polyp detection and characterization. This is an upcoming area of gastroenterology, which has already reached the doorstep of practicing clinicians and in the near future, it may bring a paradigm shift in clinical practice. It is expected that this thought-provoking review will stimulate endoscopists to take up research in this important field of application of an AI-based computer technology for endoscopic detection of gastrointestinal lesions.